Lucian's Dialogues prepared for schools - Lucian, of Samosata, 120-180; Rouse, W. H. D. (William Henry Denham), 1863-1950 (Salt Lake City, UT : Project Gutenberg, 2018)
"Lucian's Dialogues Prepared for Schools" by W. H. D. Rouse is a scholarly adaptation of ancient Greek philosophical dialogues written in the early 20th century. The text consists mainly of Lucian's witty and satirical dialogues, making them accessible for educational purposes while retaining the essence of the original content. This version is tailored for students learning Greek, simplifying some language aspects and providing notes that aid comprehension. The opening of the work introduces the structure and educational intent behind the adaptation. The preface discusses the adjustments made to Lucian's dialogues, including simplified syntax and vocabulary while preserving his stylistic humor. The author emphasizes the value of these dialogues in illustrating Greek mythology and fostering an engaging learning environment, suggesting that they serve as a memorable introduction to studying the Greek language and culture. (This is an automatically generated summary.)
Release date is 2018-08-02
Produced by an anonymous Project Gutenberg volunteer
Keywords: Dialogues, Greek; Greek language -- Study and teaching